PEMBIASAAN MENGHAFAL JUZ ‘AMMA PADA SISWA KELAS V MADRASAH IBTIDAIYAH AL-WASHLIYAH PERBUTULAN SUMBER CIREBON - Sobikhin Abddillah Hakim Nazil; Abdur Rahim (JOEL: Journal of Educational and Language Research, 2022)
The background of the research is the importance of habituation to memorize the Koran which should be done since childhood. The application of the habit of memorizing the Al-Quran is carried out every day before learning begins at MI Al-Washliyah Perbutulan, Sumber, Cirebon. is one of the madrasas that apply the use of Al-Quran habituation. The habit of memorizing the Al-Quran is done by students following what the ustadz/ustadzah says and then memorizing it. The purpose of this study was to determine the method of habituation of memorizing juz 'amma in students of MI al-washliyah Class V Perbutulan Sumber Cirebon. This type of research is a field research with a descriptive qualitative approach. In the course of collecting data, the author uses the method of interview, observation, and documentation. Meanwhile, to analyze the data obtained, the authors did it by collecting all the data, reducing the data, presenting the data and verifying the data. The results of the research that the author did, that the habit of memorizing Juz Amma at MI Al-Washliyah Class V Perbutulan Sumber Cirebon the habit of memorizing the Al-Quran was carried out before the lesson began, in the morning at 07.00 to 08.00. While the methods used in the habit of memorizing the Qur'an include the Sima'i and muraja'ah methods.